Myocardial ischemia/reperfusion injury is mediated by leukocytic toll-like receptor-2 and reduced by systemic administration of a novel anti-toll-like receptor-2 antibody. - O'NEILL, LUKE ANTHONY JOHN (My University, 2010)
Background?Reperfusion therapy for myocardial infarction is hampered by detrimental inflammatory responses partly via Toll-like receptor (TLR) activation. Targeting TLR signaling may optimize reperfusion therapy and enhance cell survival and heart function after myocardial infarction. Here, we evaluated the role of TLR2 as a therapeutic target using a novel monoclonal anti-TLR2 antibody. Method and Results?Mice underwent 30 minutes of ischemia followed by reperfusion. Compounds were administered 5 minutes before reperfusion. Cardiac function and dimensions were assessed at baseline and 28 days after infarction with 9.4-T mouse magnetic resonance imaging. Saline and IgG isotype treatment resulted in 34.5 3.3% and 31.4 2.7% infarction, respectively. Bone marrow transplantation experiments between wild-type and TLR2-null mice revealed that final infarct size is determined by circulating TLR2 expression. A single intravenous bolus injection of anti-TLR2 antibody reduced infarct size to 18.9 2.2% (P 0.001). Compared with saline-treated mice, anti-TLR2?treated mice exhibited less expansive remodeling (end-diastolic volume 68.2 2.5 versus 76.8 3.5 L; P 0.046) and preserved systolic performance (ejection fraction 51.0 2.1% versus 39.9 2.2%, P 0.009; systolic wall thickening 3.3 6.0% versus 22.0 4.4%, P 0.038). Anti-TLR2 treatment significantly reduced neutrophil, macrophage, and T-lymphocyte infiltration. Furthermore, tumor necrosis factor- , interleukin-1 , granulocyte macrophage colony-stimulating factor, and interleukin-10 were significantly reduced, as were phosphorylated c-jun N-terminal kinase, phosphorylated p38 mitogen-activated protein kinase, and caspase 3/7 activity levels. Conclusions?Circulating TLR2 expression mediates myocardial ischemia/reperfusion injury. Antagonizing TLR2 just 5 minutes before reperfusion reduces infarct size and preserves cardiac function and geometry. Anti-TLR2 therapy exerts its action by reducing leukocyte influx, cytokine production, and proapoptotic signaling. Hence, monoclonal anti-TLR2 antibody is a potential candidate as an adjunctive for reperfusion therapy in patients with myocardial infarction. (Circulation. 2010;121:80-90.)
PUBLISHED
PMID: 20026776
Keywords: Immunology; Toll-like receptors